PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETRAMPILAN BERPIKIR KRITIS SISWA KELAS IV A SDN 2 LATIHAN SPG AMBON - Putnarubun, Merlin Getdha; Mahananingtyas, Elsinora; Ritiauw, Leonid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the problem based learning model on the critical thinking skills of class IV A students at SDN 2 Latihan SPG Ambon. In this study, there was a low level of critical thinking skills in students due to the teaching and learning process still using conventional learning models, which do not support the development of students' critical thinking skills. The problem based learning model is a solution to improve the critical thinking skills of class IV A students at SDN 2 Latihan SPG Ambon. With this model, students will be accustomed to facing various problems and finding solutions through in-depth discussions and explorations. The method used is quantitative with a one-group pretest-posttest design. The research sample was all 26 class IVA students. Data collection techniques include observation, interviews, tests (pretest and posttest), and documentation. The instruments were tested for validity and reliability before being used. The method used in this writing is to apply the paired sample t test to test the hypothesis and the N-gain test to assess the effect of the learning model. Based on the results of data analysis conducted by researchers with the help of SPSS, it can be concluded; (1) For the paired sample t test, the sig. value was obtained. (2-tailed) of 0.000 < 0.05 where H0 is rejected and Ha is accepted so that it can be seen that there is an average difference between the pre-test and post-test results which means that the influence of the Problem Based Learning (PBL) learning model can improve students' critical thinking skills. (2) For the N-gain test results, a score of 0.8479 was obtained, meaning that the level of learning by applying the Problem Based Learning (PBL) learning model is in the high category to improve the critical thinking skills of class IV A students at SDN 2 Latihan SPG Ambon.